2013
DOI: 10.1016/j.jssc.2013.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Crystallinity and compositional changes in carbonated apatites: Evidence from 31P solid-state NMR, Raman, and AFM analysis

Abstract: Solid-state (magic-angle spinning) NMR spectroscopy is a useful tool for obtaining structural information on bone organic and mineral components and synthetic model minerals at the atomic-level. Raman and 31P NMR spectral parameters were investigated in a series of synthetic B-type carbonated apatites (CAps). Inverse 31P NMR linewidth and inverse Raman PO43− ν1 bandwidth were both correlated with powder XRD c-axis crystallinity over the 0.3–10.3 wt% CO32− range investigated. Comparison with bone powder crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
69
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(76 citation statements)
references
References 58 publications
6
69
1
Order By: Relevance
“…Although the specific mechanisms responsible are not clear, changes in crystallinity because of BAPN treatment is an interesting finding that warrants further investigation using more direct methods of evaluating changes to the crystalline structure. 27 Another study demonstrated no effects on crystallinity/maturity with BAPN treatment, 13 but these conflicting data may be due to differences in dose (B780 vs 300 mg kg À 1 ), method of delivery (dietary vs subcutaneous injection), animal model (rat vs mouse) and anatomical site (vertebral crosssection vs native surface of femur).…”
Section: Discussionmentioning
confidence: 99%
“…Although the specific mechanisms responsible are not clear, changes in crystallinity because of BAPN treatment is an interesting finding that warrants further investigation using more direct methods of evaluating changes to the crystalline structure. 27 Another study demonstrated no effects on crystallinity/maturity with BAPN treatment, 13 but these conflicting data may be due to differences in dose (B780 vs 300 mg kg À 1 ), method of delivery (dietary vs subcutaneous injection), animal model (rat vs mouse) and anatomical site (vertebral crosssection vs native surface of femur).…”
Section: Discussionmentioning
confidence: 99%
“…Positional disorder affects the length, and thus the strength and vibrational frequency, of C-O bonds (Bischoff et al, 1985). An increase in disorder leads to an increase in the distribution of C-O bond lengths, causing an increase in ν 1 peak width (Bischoff et al, 1985;Addadi et al, 2003;Lin et al, 2007;Wang et al, 2012;McElderry et al, 2013;Perrin et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Hydroxyapatite (HA) is the main inorganic component of human bone mineral, and the content of carbonate in human bone mineral is about 5-8 wt % [1, 2]. Carbonate ions in carbonated hydroxyapatites (CHA) substitute both the phosphate and hydroxyl sites of the HA structure and each is called A-type CHA and B-type CHA, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The characteristic peaks at 428 and 588 cm−1 were assigned to υ2 and υ4 mode, respectively [28]. As the carbonate content increases, the strongest symmetric stretch υ1 mode of PO4 3− at 960 cm−1 becomes broader, indicating the decrease of crystallinity of apatite lattices [1,29]. The peak at 1070 cm−1 can be assigned to the B-type υ1 CO3 2− mode [30, 31].…”
mentioning
confidence: 99%